Evaluation of physico-chemical properties of developed pasta fortified with Moringa olifera and Amaranth leaves powder - Namrata; Kumar , Shiv (Journal of Postharvest Technology, 2023)
Malnutrition is turning into a serious problem in the world due to a lack of nutrient-rich diets. A staple foods like pasta, is incredibly popular but due to low in essential nutrients, it is not regarded as a healthy food. In order to increase the nutritional value of pasta, its fortification with nutrients rich sources like underutilized leafy vegetables are essential, effective and affordable approach. The current study involves the development of pasta fortified with Moringa olifera leaves powder (MLP) and Amaranth leaves powder (ALP) in different ratio which is then followed by sensory evaluation using a 9-point hedonic scale. Across all treatments groups in different ratio, C: ALP6% and C: MLP6% were scored highest sensory acceptability in comparison to other combinations. These best selected ratio were further used to evaluate their physico chemical properties for understanding nutrients content profile. According to results, by adding these underutilized vegetables, it enhanced the nutritional value of pasta as compare to control. The current study suggested that the fortification of pasta with ALP and MLP may function as a natural health promoter and might have the potential to reduce the incidence of malnutrition in India and around the world.